2021
DOI: 10.1097/iop.0000000000002030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations, Management and Outcomes of Rhino-Orbital-Cerebral Mucormycosis (ROCM) Following COVID-19: A Multi-Centric Study

Abstract: Purpose: To report clinical presentations and factors affecting outcomes in rhino-orbital-cerebral mucormycosis following COVID-19. Methods: Retrospective multi-centric interventional case series of 58 eyes with rhino-orbital-cerebral mucormycosis. Demography, clinical parameters and management outcomes were noted. Factors affecting outcome and mortality were analyzed. Outcome was defined as favorable when complete resolution or stabilization without further progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 37 publications
13
77
0
Order By: Relevance
“…Contrast enhanced MRI has been proved to be a superior imaging technique over Contrast enhanced CT. ( 9) MRI was the preferred modality to monitor the extent of the disease The latest retrospective series on CAM from a geographically different location published by T.V. Dave et al (15) analysed 58 cases and noted that Intracranial extension was seen in 33%, comparable to 22.85% in current study. (p = 0.2).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Contrast enhanced MRI has been proved to be a superior imaging technique over Contrast enhanced CT. ( 9) MRI was the preferred modality to monitor the extent of the disease The latest retrospective series on CAM from a geographically different location published by T.V. Dave et al (15) analysed 58 cases and noted that Intracranial extension was seen in 33%, comparable to 22.85% in current study. (p = 0.2).…”
Section: Discussionsupporting
confidence: 61%
“…The most common side effects noted included chemosis (85%), pain (60%), and proptosis (15%). In the recent reports published on CAM, retrobulbar amphotericin was given in one patient in the recent study by Dave et al, (15) and they reported radiological resolution with uneventful follow up at 6 months of follow up. Although there is paucity of literature on the safety and e cacy pro le of the treatment method, we found that retrobulbar Amphotericin injection, when indicated, caused radiological resolution in atleast 50% patients after 1 cycle of therapy and in 65% patients after 2 cycles.…”
Section: Discussionmentioning
confidence: 94%
“…23 Steroidinduced diabetes is known to be to be an independent risk factor for invasive fungal infections, such as mucormycosis. 24 Also, cases of mucormycosis that received corticosteroids during COVID-19 treatment are shown to be associated with poorer outcomes. 25 Sen et al reported that in their series of patients of ROCM, 98% of the patients who developed ROCM showing complete ptosis of the left eye.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 15 studies had confirmed the role of diabetes in CAM [ 57 ]. Managing diabetes is thus crucial for controlling both COVID-19 and CAM [ 58 , 59 ].…”
Section: Identifying Risk Factors and Implementing Preventive Measuresmentioning
confidence: 99%